AUTOGENIC TRAINING RELAXATION HELPING POSTPARTUM MOTHERS TO ACHIEVE SUCCESSFUL BREASTFEEDING ON EARLY LACTATION PERIOD - Farida Juanita (Universitas Airlangga, 2017)
Introduction: The numbers of breastfeeding failures are mostly caused by mothers` disbelief to themselves. One method that can be done to overcome these problems in accordance with the self-care nursing theory is the autogenic training relaxation. This method teaches mothers to be self-sufficient in building a positive intention and motivation to help the process of breastfeeding. This study aimed to examine the influence of autogenic training relaxation to the effectiveness of breastfeeding and the enhancement of breast milk volume on maternal postpartum. Method: By using an experimental posttest only-non equivalent control group design, 26 samples were taken based on the criteria and divided into two groups by matching technuiqe. autogenic training was given through MP3 Player for 3 weeks. Post-test observation conducted on the third week by home visit. Via Christi Breastfeeding Assessment Tool Jan Riordan modifications used to assess the effectiveness of breastfeeding, and to measure the milk ejection volume, used weighing test using electronic baby scales. Data were analyzed using one-tailed independent t test with α ≤ 0.05. Result: The analysis showed that mothers who did autogenic training relaxation could breastfeed more effectively and had greater average volume of milk ejection than the control group (p = 0.000 and p = 0.001). Discussion: It can be concluded that autogenic relaxation training techniques affect the effectiveness of breastfeeding and breast milk volume. These results can be considered that autogenic training as an intervention in program of support for breastfeeding mothers.